Optimization of Culture Conditions for Growth of Marine Phytoplankton - Kunguma Kannika Maharajan; Panneerselvam Karthikeyan; Shambanagouda Rudragouda Marigoudar; Krishna Venkatarama Sharma; Kasthuri Revathi (Journal of Tropical Life Science, 2020)
The present study investigated the optimum levels of ambient temperature, salinity and light intensity for the growth of marine diatoms and microalgae. The marine diatoms Thalassiosira subtilis, Entomoneis paludosa and microalgae Isochrysis galbana were optimized for the growth. Subcultures were prepared in filtered natural seawater enriched with f/2 media for diatoms and Conway media for I.galbana. Cultures were grown under three different levels of three parameters consists of 27 combinations in 96 well plates. Ten replicates of cultures were maintained for each combination of ambient levels. The algal density was determined by spectrometric absorbance of culture at 680 nm. Likewise, the growth was estimated from the rate of increase in the absorbance values over a period of time. The durations of growth differed between the species. The I.galbana was grown for prolonged culture duration up to 15 days followed by E.paludosa with 12 days and T.subtilis with 8 days. Levels of ambient temperature and light intensity are the driving parameters for optimum growth of the species studied while the optimum salinity of 30 psu was observed for all species.Ambient levels of 28 °C, 30 psu and 2500 lux were found optimum for the growth of T. subtilis and E.paludosa attained its optimum growth at 24 °C, 30 psu and 2500 lux. The higher light intensity (4500 lux) hasenhanced the growth of I.galbanaalong with 24 °C of temperature and 30 psu of salinity.